The Effect of Counselling Training on Differentiation of Self, Religious Quest and Epistemological Development - John Meteyard; Kirsty Andersen (Psychotherapy and Counselling Journal of Australia)
This study used three developmentally-orientated psychological constructs – Differentiation of Self [DoS], Religious Quest [Quest] and Epistemological Development [ED] – to evaluate the effectiveness of the training programs of one faith-based higher education institution in facilitating the interpersonal, intrapersonal, spiritual and epistemological maturation of counselling students. Seventy-four postgraduate and undergraduate counselling students participated in a quantitative research study in which the number of semesters they had been studying counselling and the number of subjects they had completed within their course of study were used as predictors of their levels of DoS, Quest and ED. Results indicated that the number of semesters of study was positively correlated with levels of one DoS subscale (Emotional Reactivity) and one ED subscale (Empathy), as well as being inversely predictive of a second ED subscale (Dualism). Both number of semesters of enrolment and number of units completed were significant positive predictors of Quest and one of its component dimensions (perception of doubt as positive).